HYDROTHERMAL ALTERATION ZONES DETECTION IN LIMNOS ISLAND, THROUGH THE APPLICATION OF REMOTE SENSING - Anifadi, A.; Parcharidis, Is.; Sykioti, O. (Bulletin of the Geological Society of Greece, 2016)
In this study we use Landsat 8 OLI satellite imagery in order to identify and map alteration zones in Limnos island (N. Aegean, Greece). Pre-processing included sea and vegetation masking. In order to enhance spatial resolution, data fusion to 15m is performed. A lineament map is extracted from the panchromatic image that gives the general tectonic view of the island. The detection and mapping of alteration minerals is performed using specific band ratios and consequent composite images. The colour composite using bands 10, 11, 7 (RGB) show the spectral signature and general distribution of silica. Band ratios 6/7, 4/2, 6/5, reveal alteration zones containing iron oxides, clay alteration and ferrous minerals correspondingly. The aforementioned analysis has shown that hydrothermally alteration areas in Limnos are located in the west part of the island and at the Fakos Peninsula, Sardes, Roussopouli and Paradeisi hill. These areas are compared and validated with the reported field work. We conclude that hydrothermal alteration zones can indeed be detected and mapped using medium resolution satellite multispectral data. However, for the identification and mapping of specific types of rocks and minerals, a sensor with high spectral resolution is required.